Reproductologist’s current views on etiopathogenesis and treatment of uterine leiomyoma - N. V. Avramenko; D. E. Barkovsky; O. V. Kabachenko; D. V. Letsin (Zaporožskij Medicinskij Žurnal)
Aim. To analyze specialized scientific literature for compilation of data about contemporary views on the uterus leiomyoma etiopathogenetic features, its clinical course and influence on woman’s reproductive function, and also to study data about modern methods of the uterus leiomyoma prophylaxis and treatment.